2013
DOI: 10.1007/s10552-013-0229-6
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and the risk of overall and fatal prostate cancer in the NIH-AARP Diet and Health Study

Abstract: Purpose Evidence on the association between coffee consumption and prostate cancer risk is inconsistent; furthermore, few studies have examined the relationship between coffee consumption and fatal prostate cancer. The aim of this study was to investigate whether coffee intake is associated with the risk of overall and fatal prostate cancer. Methods We conducted a prospective analysis among 288,391 men in the National Institutes of Health (NIH)-AARP Diet and Health Study who were between 50–71 years old at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…[5][6][7][28][29][30][31][32]38 The results from the subgroup analysis showed a strong inverse association between coffee consumption and fatal or high-grade prostate cancer risk, suggesting that coffee may be implicated in preventing progression of prostate cancer. A recent study indicated that higher prediagnostic coffee consumption was associated with a lower risk of prostate cancer recurrence/progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][28][29][30][31][32]38 The results from the subgroup analysis showed a strong inverse association between coffee consumption and fatal or high-grade prostate cancer risk, suggesting that coffee may be implicated in preventing progression of prostate cancer. A recent study indicated that higher prediagnostic coffee consumption was associated with a lower risk of prostate cancer recurrence/progression.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7]11,12,[21][22][23][24][25][26][29][30][31][33][34][35]38 Statistically significant departure from linearity was found for all studies (P ¼ 0.04; Figure 3a), but not for cohort studies (P ¼ 0.07; Figure 3b) and case-control studies (P ¼ 0.38). A 2 cups/day increment in coffee consumption level conferred an RR of 0.97 (95% CI ¼ 0.94-1.01) for overall result, 0.93 (95% CI ¼ 0.88-0.99) for cohort studies and 1.04 (95% CI ¼ 1.00-1.08) for case-control studies.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In a recent meta‐analysis of 12 case control and 9 cohort studies, the odds of prostate cancer amongst individuals in the highest category of coffee consumption were 0.91 times that in the lowest category . Evidence is, however, mixed; not all studies have found strong evidence for a link between coffee and prostate cancer . A protective effect is biologically plausible, given coffee's abundance of compounds with anti‐oxidant and anti‐inflammatory effects and reported effects on insulin levels .…”
mentioning
confidence: 99%
“…Prostate cancer is a heterogeneous disease and conducting investigations by stage, grade or fatality are important for identifying associations specific for fatal tumors or tumors that are likely to advance to metastatic disease. Unfortunately, less than half of the available cohort studies have investigated such associations . Total coffee consumption (per 1 cup/day) was not associated with risk of fatal prostate cancer in the WCRF‐CUP meta‐analysis (4 cohorts; RR, 0.97; 95% CI, 0.93–1.00) or in another meta‐analysis (4 cohorts; RR, 0.76; 95% CI, 0.55–1.06) that compared highest to lowest consumption, and a similar result was observed for advanced prostate cancer (6 cohorts; RR, 0.82; 95% CI, 0.61–1.10) .…”
Section: Discussionmentioning
confidence: 76%
“…Study differences may explain the discrepancy between our findings and those in HPFS. In EPIC, we had a narrower range of coffee intakes (inter‐quartile range, 139–665 mL/day) compared to HPFS, but other North American or European studies with similar ranges of coffee consumption to HPFS observed null findings for coffee and fatal prostate cancer . When we performed an analysis in EPIC between the 5,018 men, 46 of which develop fatal prostate cancer, who drank six or more cups (~1,418 mL) of coffee per day compared to nondrinkers, the results were null (HR, 1.04; 95% CI, 0.67–1.62).…”
Section: Discussionmentioning
confidence: 86%